Indacaterol/glycopyrronium in symptomatic patients with COPD (GOLD B and GOLD D) versus salmeterol/fluticasone: ILLUMINATE/LANTERN pooled analysis - Vogelmeier C; Zhong NS; Humphries MJ; Mezzi K; Fogel R; Bader G; Patalano F; Banerji D (International Journal of COPD, 2016)
Claus Vogelmeier,1 Nanshan Zhong,2 Michael J Humphries,3 Karen Mezzi,4 Robert Fogel,5 Giovanni Bader,4 Francesco Patalano,4 Donald Banerji5 1Department of Medicine, Pulmonary and Critical Care Medicine, University Medical Center Giessen and Marburg, Philipps-University Marburg, Member of the German Center for Lung Research (DZL), Marburg, Germany; 2State Key Laboratory, Guangzhou Institute of Respiratory Diseases, First Affiliated Hospital, Guangzhou Medical University, Guangzhou, 3Beijing Novartis Pharma Co. Ltd., Shanghai, People’s Republic of China; 4Novartis Pharma AG, Basel, Switzerland; 5Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA Background: Indacaterol/glycopyrronium (IND/GLY) is approved for maintenance treatment of adult patients with COPD. This post hoc analysis explored the efficacy and safety of IND/GLY versus salmeterol/fluticasone (SFC) in symptomatic (Global Initiative for Chronic Obstructive Lung Disease [GOLD] B and GOLD D) patients with moderate-to-severe COPD.Patients and methods: Data from LANTERN and ILLUMINATE studies were pooled and analyzed. In both studies, symptomatic COPD patients were randomized to once-daily IND/GLY 110 µg/50 µg or twice-daily SFC 50 µg/500 µg. End points were pre-dose trough forced expiratory volume in one second (FEV1), standardized area under the curve for FEV1 from 0 to 12 hours (FEV1 AUC0–12 hours), peak FEV1, peak forced vital capacity (FVC), pre-dose trough FVC, Transition Dyspnea Index (TDI) total score, St George’s Respiratory Questionnaire total score, rescue medication use and safety.Results: A total of 1,263 patients were classified as either GOLD B (n=809) or GOLD D (n=454). At week 26, IND/GLY demonstrated statistically significant improvement in all lung function parameters versus SFC in patients in both the GOLD B and GOLD D subgroups. TDI total score and rescue medication use were significantly improved with IND/GLY versus SFC in the overall population and in the GOLD B (TDI total score only) and GOLD D (rescue medication only) subgroups. IND/GLY also reduced the rate of exacerbations in the pooled population. Overall safety profile was comparable with a higher incidence of pneumonia in the SFC-treated group.Conclusion: In this pooled analysis, IND/GLY demonstrated superior efficacy compared with SFC in patients in the GOLD B and GOLD D subgroups and supported its use in symptomatic COPD patients. Keywords: COPD, exacerbation, LABA/LAMA, LABA/ICS, lung function